2012
DOI: 10.1158/1055-9965.epi-11-1159
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Position and Stage of Cervical Cancer in Danish Women Diagnosed 2005 to 2009

Abstract: Background: To reduce social disparities in cervical cancer survival, it is important to understand the mechanisms by which social position influence cancer prognosis. We investigated the relations between socioeconomic factors, comorbidity, time since last Papanicolau smear, and stage at diagnosis in Danish women with cervical cancer. Results: The risk for advanced (stage II-IV) compared with early-stage cancer (stage I) was increased for women with short and medium education (OR ¼ 2.40; 1.67-3.45 and 1.76; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 31 publications
2
43
0
1
Order By: Relevance
“…Recent Danish studies found associations between individually measured level of education and advanced stage at diagnosis of breast, lung, rectal and cervical cancers and non-Hodgkin lymphoma, but not for colon cancer [16][17][18][19][20]. We also found a trend of an association between level of education and stage at diagnosis.…”
Section: Education and Stage At Diagnosissupporting
confidence: 53%
See 1 more Smart Citation
“…Recent Danish studies found associations between individually measured level of education and advanced stage at diagnosis of breast, lung, rectal and cervical cancers and non-Hodgkin lymphoma, but not for colon cancer [16][17][18][19][20]. We also found a trend of an association between level of education and stage at diagnosis.…”
Section: Education and Stage At Diagnosissupporting
confidence: 53%
“…As education has been linked to an individual's level of resources, cognitive function and perception of health education messages [21,22], better educated women may be more aware of symptoms and react accordingly. Thus, the indication of an association between educational level and stage at diagnosis might be due to differences in knowledge about unexpected post-menopausal bleeding or in the ability to communicate symptoms to a general practitioner or other medical specialist [19].…”
Section: Education and Stage At Diagnosismentioning
confidence: 99%
“…The cca risk among immigrants appears to be lower with length of time lived in Canada, which might be attributable to a greater likelihood of screening use in long-term immigrants than in recent immigrants 9,19,20 . Language barriers 10 and lower education level 10,12,21 are associated with greater risk of cca, likely because of poor use of Pap screening 9,10,20,22,23 . The study results also echo earlier findings 9,10,20 in highlighting the importance to appropriate screening of having a regular doctor.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that lower SEC women were more influenced by the story is encouraging, as there is higher incidence of cervical cancer in more deprived groups and this is partly explained by lower attendance at cervical screening. 23,24 It can be difficult to engage these groups with interventions that aim to increase screening uptake 25 and studies have shown that narrative approaches can effectively increase screening participation among low SEC women. 26 The potential for narrative communication to decrease social inequalities in attendance should be explored further.…”
Section: Discussionmentioning
confidence: 99%